ANALISIS PENINGKATAN KEMAMPUAN STRATEGI PEMASARAN DENGAN MENGGUNAKAN TEKNOLOGI INFORMASI PADA BISNIS PERHOTELAN DI KOTA BATAM - Daniel Apdianto Herman (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
The development of the hospitality business in Batam is increasingly making competition and competition between hotels tighter. Competition and competition make the management of hotels must have good marketing strategy skills so that they can increase the sales volume and room occupancy rate of their hospitality business. The reason of this observe is to discover how information technology can improve the ability of marketing strategies in terms of sales volume and room occupancy rates in the hospitality business. The sampling method of this research was performed through the usage of purposive sampling with the wide variety of respondents as many as 50 people who were taken intentionally. The conclusion tool used is SWOT analysis to take benefit of possibilities and maximize strengths, lessen weaknesses and additionally avoid threats. The Strengths-Opportunities (SO) strategy is implemented using brand positioning through the development of hotel websites, maximizing cooperation with travel agents by providing easy booking using online technology applications. In the ST strategy, it is applied by conducting a comparative analysis of room quality and room prices with star-class hotels through information technology, using promotional media supported by technological advances. In the WO strategy by minimizing weaknesses by analyzing cost components, renovating rooms with the help of using information technology. Then the WT strategy that is carried out is to improve the quality of service by using mobile check-in)